Body image, perceived stress, and resilience in military amputees of the internal armed conflict in Colombia - Herrera Moreno, Daniela (Editorial Bonaventuriana, 2018)
The objective of this study was to determine the levels and the relationship between body image satisfaction, perceived stress and resilience in soldier amputee victims of the internal armed conflict in Colombia. It was a quantitative, cross-sectional study of correlational scope, with the participation of 22 Colombian soldiers who were victims of the internal armed conflict and with some degree of amputation. For each soldier, the Multidimensional Body Self-relations Questionnaire (MBSRQ), Perceived Stress (EEP-14) and the Connor-Davidson Resilience Scale (CD-RISC 10) were applied. The results show high scores in behaviors aimed at maintaining physical fitness, self-assessed physical attractiveness and physical appearance, low scores in stress and scores with high trends in resilience, as well as a negative correlation between stress and conducts aimed to maintain physical fitness.